Dopamine in Autism Spectrum Disorders—Focus on D2/D3 Partial Agonists and Their Possible Use in Treatment - Mandic-Maravic, Vanja; Grujicic, Roberto; Milutinovic, Luka; Munjiza-Jovanovic, Ana; Pejovic-Milovancevic, Milica (Frontiers in Psychiatry, 2022)
Autism spectrum disorders (ASD) are a group of disorders characterized by impairment in social communication, as well as repetitive and stereotyped behaviors. ASD aetiology is very complex, including the effect of both genetic and environmental factors. So far, no specific treatment for the core symptoms of ASD has been developed, although attempts have been made for the treatment of repetitive behavior. The pharmacological treatment is aimed at treating non-specific symptoms such as irritability and aggression. Recent studies pointed out to the possible role of altered dopamine signalling in mesocorticolimbic and nigrostriatal circuits in ASD. Also, several research pointed out to association of dopamine receptors polymorphism and ASD, specifically repetitive and stereotyped behavior. In this paper, we will provide a review of the studies regarding dopamine signalling in ASD, existing data on the effects of D2/D3 partial agonists in ASD, possible implications regarding their individual receptor profiles and future perspectives of their possible use in ASD treatment.